Tumor-derived exosomes in the cancer immune microenvironment and cancer immunotherapy. (1st November 2022) - Tang, Qiushi; Yang, Shuo; He, Guangpeng; Zheng, Hongyu; Zhang, Sheng; Liu, Jiaxing; Wei, Shibo; Fan, Qing; Peng, Xueqiang; Li, Xinyu; Zhang, Dewei; Yang, Liang; et al.
Abstract: Tumor-derived exosomes (TDEs) are key immune regulators in the tumor microenvironment. They have been shown to reshape the immune microenvironment and prevent antitumor immune responses via their immunosuppressive cargo, thereby determining responsiveness to cancer therapy. By delivering suppressive cargo to the immune cells, TDEs directly or indirectly influence the functions and antitumor activities of immune cells. TDE-based therapy is emerging as a cutting-edge and promising strategy for inhibiting tumor progression or enhancing antitumor immunity. Therefore, in this study, we reviewed the mechanism by which TDEs regulate immune cells and their applications in immunotherapy. Highlights: We summarized the formation, function and heterogeneity of tumor-derived exosomes (TDEs). TDEs-based therapy represents a predominant strategy with a promising future. TDEs directly or indirectly influence the functions and antitumor activities of immune cells. TDEs have specific applications in neoantigen tumor vaccines and immune checkpoint blockade therapies.